2020
DOI: 10.1136/bmjopen-2019-034553
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals knowledge, attitude and practice of adverse drug reactions reporting in Ethiopia: a cross-sectional study

Abstract: ObjectiveThis study aimed to assess the knowledge, attitude and practice of adverse drug reactions (ADRs) reporting and identify factors associated with ADRs reporting among healthcare professionals (HCPs) working in Tigray region, Ethiopia.Materials and methodsA cross-sectional study was conducted between January and March of 2019 in a tertiary care hospital in Tigray region, Ethiopia. A self-administered, pretested questionnaire was administered to HCPs. Data were summarised using descriptive statistics. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 30 publications
6
51
3
Order By: Relevance
“…From 13 reviewed studies, one study [ 31 ] and two studies [ 23 , 25 ] did not report the knowledge and attitudes of health care professionals towards ADR reporting, respectively. The knowledge and attitude of health care professionals towards ADR reporting ranged from 22.68% to 60.33% and 47.22% to 67.14%, respectively, with an average of 41.50% and 57.18% ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…From 13 reviewed studies, one study [ 31 ] and two studies [ 23 , 25 ] did not report the knowledge and attitudes of health care professionals towards ADR reporting, respectively. The knowledge and attitude of health care professionals towards ADR reporting ranged from 22.68% to 60.33% and 47.22% to 67.14%, respectively, with an average of 41.50% and 57.18% ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is similar to that of Gidey et al, who reported that 68% of HCPs did not report ADRs, even when they encountered them. 21 On analysing the factors influencing the incident reporting, we found that 66% of the faculty and HCPs agreed that the "possible negative effect on the relationship with employees" was the most common factor influencing incident reporting. Khan observed that only 10% of HCPs perceived the "lack of confidence to discuss an ADR with a colleague" as a factor discouraging ADR reporting.…”
Section: Discussionmentioning
confidence: 93%
“…At the same time, the majority did not even send any ADR during their practice period despite the ADR reporting system's vital opinions, which reliable with previous studies. [9,10,13,14,18,19,[21][22][23]25,26,32,33,[44][45][46][47][48][49] Further, it might be the ADR not readily obtainable at the front medical disk or nursing station at the wards or clinics. The ADR reporting system was incompetently implemented with most practice elements related to inadequate knowledge of physicians of the practice or not practice or seldom doing the exercise of ADR reporting system and contained with another study.…”
Section: Discussionmentioning
confidence: 99%
“…The second part had selected practice rudiments of the ADR system responsible for reporting ADR, the number of ADR reporting and the methods of ADR reporting system from previous literature. [9,12,13,15,19,[21][22][23][24]26,[28][29][30][31][32][33][34][35] The 5-point Likert response scale system was employed with closed-ended questions. The sample calculated as crosssectional study according previous literature with the confidence level 95% with z score of 1.96, margin of error (5-6.5%), unlimited populations size, populations' percentage (50%) and drop-out rate (10%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation